Cognitive, psychosocial, and behaviour gains at age 31 years from the Jamaica early childhood stimulation trial. (17th August 2021) - Walker, Susan P.; Chang, Susan M.; Wright, Amika S.; Pinto, Rodrigo; Heckman, James J.; Grantham‐McGregor, Sally M.
Abstract : Background: There is little evidence on adult benefits from early childhood interventions in low and middle‐income countries. We assessed adult cognition, psychosocial skills and behaviour from a stimulation trial conducted in Jamaica. Methods: Children with stunted growth (height‐for age <−2 SD of references) aged 9–24 months were enrolled in a two‐year randomised‐controlled trial of nutritional supplementation and/or stimulation. At mean age 31.79 ( SD 0.40) years, 95 of 127 participants (74.8%; 53.7% male) were assessed. Children without stunted growth were also followed as a comparison group (64 of 84 participants, 76.2%). Measurements included IQ, executive function, mental health, psychosocial skills, personality traits and risk behaviours. A block permutation test, valid for small sample sizes, was used. Analyses accounted for the randomisation protocol, multiple hypothesis testing and attrition. Results: Treatment group participants (stimulation intervention with or without supplementation, n  = 48) had significantly greater IQ (Hedges g effect size 0. 57; 95%CI 0.20, 0.95) and cognitive flexibility (0.61; 0.25, 0.98) compared with no‐treatment (no‐intervention and supplementation only, n  = 47). They also had reduced depressive symptoms (0.61; 0.28, 1.00), increased grit (0.53; 0.16, 0.92) and conscientiousness (0.66; 0.31, 1.07), lower substance use (rank mean score, 0.45; 0.08, 0.81) and risk taking related to health and work (0.64; 0.27, 1.00). There were 18 significant outcomes of 33 assessed. Comparison participants had higher IQ than no‐treatment (1.17; 0.81, 1.54) and treatment groups (0.62; 0.18, 1.07); and better executive function, lower social inhibition and risk taking than the no‐treatment group. Conclusions: The wide‐ranging benefits at 31 years from the stimulation intervention supports investment in larger scale programmes to promote early childhood development in disadvantaged children. The lower IQ in the treatment group compared with comparison participants, emphasises the need for continued efforts to prevent early childhood growth retardation.